INCOME AND WEALTH IN GHANA: ISSUES OF DISTRIBUTION AND DETERMINANTS - Afful, Jr. B.; Nunoo, J.; Arthur-Biney, A. (UDS International Journal of Development, 2019)
Inequality has been a major problem facing many countries, with Ghana not being an exception. The enormous problems of inequality have engendered worldwide fight (both physical and intellectual) towards its elimination. Unfortunately, the debate on inequality and its decomposition has often beenbased on income or consumption inequality with little attention onwealth inequality. To get the complete picture of the inequality levels in Ghana, it is appropriate to look at inequality from the wealth angle and then compare the two. Using the Ghana Living Standards Survey of 2006/07 and 2012/13, this study sought to compare the patterns and trends of income and wealth inequality, decompose the Gini coefficient by subgroup and by source, find the marginal effects and then finally look at the effect of economic dependency on income and wealth. The Principal Component Analysis (PCA) was used to calculate the wealth index and the Gini coefficient was used to calculate both wealth and income inequality. The Theil index was used to decompose both income and wealth inequality across all the geographical areas, gender, age, income and asset. The Gini coefficient was further decomposed and their partial derivatives used as marginal effects. The Ordinary Least Squares (OLS) was used to find the effect of economic dependency on income and wealth. Using the Gini coefficient, it was realized that there was a decrease in wealth inequality whereas income inequality increased between 2006 and 2013. However, there were still wide disparities across the geographical areas in terms of either income or household assets. The source component decomposition analyses suggest that income inequality in the urban, rural, male and female have increased over the study period while that of the female has reduced. Asset inequality on the other hand, decreased in the urban but increased around rural, male and female. The study also shows that economic dependency reduces income but increases household assets. This study therefore advocates for policies that will address the needs of the deprived areas through creation of jobs and provision of basic social amenities in order to close the income and the asset inequality gap in Ghana. Keywords: Income, Asset, Inequality, Dependency, Ghana